2018 20th International Symposium on Symbolic and Numeric Algorithms for Scientific Computing (SYNASC) 2018
DOI: 10.1109/synasc.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Extremal Graphs with Respect to the Modified First Zagreb Connection Index

Abstract: Topological indices (TIs) have an important role in studying properties of molecules. A main problem in mathematical chemistry is finding extreme graphs with respect to a given TI. In this paper extremal graphs with respect to the modified first Zagreb connection index for trees in general and for trees with given number of pendants, for unicyclic graphs with or without a fixed girth and connected graphs are determined, using methods with higher degree of generality with respect to the transformation technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Some recent extremal results on the topological index ZC Ã 1 can be found in. [25,26] The purpose of the present study is to extend the main results of the paper, [10] or more precisely, to find the alkanes with the first three maximal and the first three minimal ZC Ã 1 values from the class of all n-vertex molecular trees.…”
Section: Introductionmentioning
confidence: 90%
“…Some recent extremal results on the topological index ZC Ã 1 can be found in. [25,26] The purpose of the present study is to extend the main results of the paper, [10] or more precisely, to find the alkanes with the first three maximal and the first three minimal ZC Ã 1 values from the class of all n-vertex molecular trees.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, Problem 1.1 is well-defined for 3 ≤ k ≤ n − 1. Also, Ducoffe et al [30] proved that the star graph S n has the maximal ZC * 1 value among all the nvertex trees, which implies that S n has the maximal ZC * 1 value among all the members of T n,n−1 as well. Consequently, while solving Problem 1.1 concerning maximal ZC * 1 value, we will consider the constrain 3 ≤ k ≤ n − 2, and while solving the remaining part of Problem 1.1 we will assume 3 ≤ k ≤ n − 1.…”
Section: Problem 11: Characterize All the Graphs With The Maximal/mimentioning
confidence: 99%
“…It needs to be mentioned here that the index ZC * 1 was referred as the third leap Zagreb index in [26]. After appearance of the papers [14,26], mathematical properties of the modified first Zagreb connection index ZC * 1 have been studied in a considerable number of papers [26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…ey also reported that it has more precise values of the correlation coefficients of various octane isomers. Du et al [22], Ducoffe et al [23], and Shao et al [24] determined extremal alkanes and cycloalkanes under different conditions using this ZCI. Zhu et al [25] established the lower bound by using the modified first ZCI of trees in terms of their order and maximum degree.…”
Section: Introductionmentioning
confidence: 99%